Social Engineering : Hacking Systems, Nations, and Societies. - Erbschloe, Michael, 1951- (CRC Press LLC, 2019)
This book analyzes of the use of social engineering as a tool to hack random systems and target specific systems in several dimensions of society. It shows how social engineering techniques are employed well beyond what hackers do to penetrate computer systems. And it explains how organizations and individuals can socially engineer their culture to help minimize the impact of the activities of those who lie, cheat, deceive, and defraud. After reading this book, you'll be able to analyze how organizations work and the need for security to maintain operations and sustainability, and be able to identify, respond to and counter socially engineered threats to security.